Protective effects of Ephedra sinica extract on blood–brain barrier integrity and neurological function correlate with complement C3 reduction after subarachnoid hemorrhage in rats. (16th November 2015) - Zuo, Shilun; Li, Wenyan; Li, Qiang; Zhao, Hengli; Tang, Jun; Chen, Qianwei; Liu, Xin; Zhang, John H.; Chen, Yujie; Feng, Hua
Highlights: Ephedra Sinica alleviated neurological deficits and cortex cell death after SAH. Ephedra Sinica reduced brain edema and blood brain barrier permeability after SAH. Ephedra Sinica inhibited the deposition and expression of compliment C3 after SAH. Ephedra Sinica increased sonic hedgehog and osteopontin expressions after SAH. Ephedra Sinica reduced matrix metalloproteinase-9 expression after SAH. Abstract: Early brain injury, which is associated with brain cell death, blood–brain barrier disruption, brain edema, and other pathophysiological events, is thought to be the main target in the prevention of poor outcomes after subarachnoid hemorrhage (SAH). Emerging evidences indicates that complement system, especially complement C3 is detrimental to neurological outcomes of SAH patients. Recently, Ephedra sinica extract was extracted and purified, which exhibits ability to block the activity of the classical and alternative pathways of complement, and improve neurological outcomes after spinal cord injury and ischemic brain injury. However, it is still unclear whether Ephedra sinica extract could attenuate early brain injury after SAH. In the present study, a standard endovascular perforation model was used to produce the experimental SAH in Sprague-Dawley rats. Ephedra sinica extract (15 mg/kg) was orally administrated daily and evaluated for effects on modified Garcia score, brain water content, Evans blue extravasation and fluorescence, cortex cell death by TUNEL staining, and the expressions of complement C3/C3b, activated C3, sonic hedgehog, osteopontin and matrix metalloproteinase-9 by western bolt and immunofluorescence staining. We founded that the Ephedra sinica extract alleviated the blood–brain barrier disruption and brain edema, eventually improved neurological functions after SAH in rats. These neuroprotective effects was associated with the inhibition of complement C3, possibly via upregulating sonic hedgehog and osteopontin signal, and reducing the expressions of matrix metalloproteinase-9. Taking together, these observations suggested complement C3 inhibition by the Ephedra sinica extract may be a protective factor against early brain injury after SAH.